Effects of empty fruit bunch biochar and nitrogen-fixing bacteria on soil quality and growth of sweet corn - Abdulrahman, Diyar Kareem (2015)
There has been an increasing interest in biochar research as soil amendments to improve soil properties leading to improve most of plant growth in a sustainable agriculture. Tropical soil is generally unfertile unit, low organic matter, plant nutrients, acidic and low microorganisms that affect crop production. Addition of biochar such as empty fruit bunch (EFB) could improve the soil fertility. Laboratory and glasshouse studies were conducted with the following objectives, i) to determine the effect of soil sterilization, EFB biochar and N2-fixing bacteria Stenotrophomonas sp. (Sb16) on indigenous soil microbial population, enzyme activity and soil chemical properties, and ii) to determine the effect of EFB biochar and N2-fixing bacteria Sb16 on growth and nutrient uptake of sweet corn. Five rates of EFB biochar (0, 0.25, 0.5, 0.75 and 1%) were applied to sterilized and non-sterilized soil either with or without N2-fixing bacteria Sb16 and incubated for 40 days under laboratory condition. The factorial study was arranged in a Complete Randomized Design (CRD) with 3 replications. Microbial population, enzyme activity and chemical properties of soil were determined at the end of incubation. Sweet corn was grown in pots containing 6 kg soil and applied with the 5 levels of EFB biochar (0, 5, 10, 15 and 20 t/ha) either with or without bacteria Sb16. Plants were sampled at tasseling stage and analyzed for dry biomass, chlorophyll content and nutrient uptake. Soil samples were analyzed for soil biochemical and microbiological properties. Results of laboratory study showed that application of EFB biochar at 0.5% without inoculation and 0.25% with N2-fixing bacteria Sb16 in both soils significantly increased population of soil bacteria, fungi, actinomycetes and N2-fixing bacteria (NFB), enzymes (urease, acid phosphatase and fluorescein diacetate hydrolysis (FDA) activity), and soil chemical properties (pH, organic C, total N, available P and exchangeable K, Ca and Mg. A glasshouse experiment showed that application of EFB biochar at 5 t/ha and N2-fixing bacteria Sb16 significantly (P<0.05) improved growth of corn (shoot and root biomass, root length, root volume, plant height and leaf chlorophyll content, nutrient uptake), soil microbial populations, FDA and selected soil chemical properties. The EFB biochar at 5 t/ha and N2-fixing bacteria Sb16 stimulated soil quality and plant growth. Addition of high EFB rates (15 and 20 t/ha) to soil negatively affected all the observed parameters. Addition of EFB biochar to soil with N2-fixing bacteria may be an alternative solution in improving nutrients, enzymes and diversity of microorganisms in soil and thus led to improve plant growth. The studies showed that application of EFB biochar at 5 t/ha or 0.25% with N2-fixing bacteria Sb16 and 10 t/ha or 0.5% without bacteria inoculated improved corn growth and the quality of soil for sustainable corn production.